Synthesis method of vinyl acetate, catalyst for synthesizing vinyl acetate and preparation method of catalyst
By adding Pd, Group IB metals and alkali metal acetate to the catalyst for synthesis of ethylene acetate in the gas-phase method, and controlling the acidic site ratio on the catalyst surface, the problem of low catalyst selectivity is solved and higher selectivity and synthesis efficiency is achieved.
Patent Information
- Application Number
- CN202311292855.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-08
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-10-08
AI Technical Summary
In the prior art, the catalyst selectivity of ethylene acetate is low in ethylene gas phase, resulting in poor synthesis efficiency and product quality.
A novel ethylene acetate catalyst is provided, which includes a support and a support-supported Pd, IB metal and alkali metal acetate. The ratio of the strong acid site content to the weak acid site content on the catalyst surface is 0.15-5, and the selectivity of the catalyst is improved by a specific preparation method.
It significantly improves the space-time yield of ethylene acetate products and the selectivity of synthesis reactions, and improves the performance and industrial application value of the catalyst.
Smart Images

Figure BDA0004482072420000161
Abstract
Description
Technical Field
[0001] The present invention relates to a catalyst for synthesizing vinyl acetate and a preparation method thereof, and a method for synthesizing vinyl acetate. Background Art
[0002] As an important organic monomer, vinyl acetate (VAc) is an important raw material for synthesizing chemical products such as polyvinyl alcohol (PVA), polyvinyl acetate (PVA), ethylene-vinyl acetate copolymer resin (EVA), vinyl acetate-vinyl chloride copolymer (EVC) and polypropylene comonomer. It is widely used in synthetic fibers, leather processing, films, vinylon, adhesives, coatings and other fields. Among them, the ethylene gas phase method is one of the most important methods for producing VA in industry at present, which has the advantages of high energy utilization rate and low environmental harm. Especially in recent years, with the opening of the technical route of biomass to ethanol and further dehydration to ethylene, the synthesis of VAc by ethylene gas phase method has received more attention.
[0003] At present, the industrial synthesis of VAc from ethylene by gas phase method mainly uses palladium-gold / potassium acetate / silicon dioxide as catalyst, and the palladium site on the catalyst surface is the main active site. During the reaction, ethylene, oxygen and acetic acid are used as raw materials, and the gas phase catalytic reaction is used to produce vinyl acetate, water and carbon dioxide as a byproduct. The temperature of the reactor shell side of the reaction can be about 100-180°C, the reaction pressure is about 0.5-1.0MPa, and the gas volume space velocity is about 500-3000hr -1 .
[0004] At present, the raw materials used in the industrial synthesis of vinyl acetate by ethylene process are mainly oxygen, ethylene, acetic acid and some nitrogen, such as the patent CN101391215A of Saudi Basic Industries Corporation. The selectivity of the catalysts in these methods is low. Therefore, in order to solve the above problem, we have developed a new type of vinyl acetate catalyst to effectively solve the problem of low catalyst selectivity. Summary of the invention
[0005] The purpose of the present invention is to overcome the problem of low catalyst selectivity in the prior art and to provide a novel vinyl acetate catalyst and a vinyl acetate synthesis method, wherein the catalyst has a higher space-time yield and target product selectivity.
[0006] In order to achieve the above-mentioned object, the present invention provides a catalyst for synthesizing vinyl acetate on one hand, which comprises a carrier and Pd, a Group IB metal and an alkali metal acetate loaded on the carrier, wherein the ratio of the content of strong acid sites to the content of weak acid sites on the surface of the catalyst is 0.15 to 5, preferably 0.2 to 4.
[0007] A second aspect of the present invention provides a method for preparing the catalyst for synthesizing vinyl acetate according to the present invention, the method comprising:
[0008] (a) immersing a catalyst support source in a solution containing a palladium source and a Group IB metal source, and drying the solution to prepare a catalyst precursor I;
[0009] (b) mixing and contacting the catalyst precursor I with a solution of a basic compound, and drying to obtain a catalyst precursor II;
[0010] (c) reducing the metal ions of catalyst precursor II and drying to obtain catalyst precursor III;
[0011] (d) impregnating catalyst precursor III with alkali metal acetate and drying to obtain catalyst precursor IV;
[0012] (e) The catalyst precursor IV is immersed in an aqueous solution containing a phosphoric acid substance, and then dried to obtain a finished catalyst.
[0013] The third aspect of the present invention provides a method for synthesizing vinyl acetate, wherein a raw gas for synthesizing vinyl acetate is subjected to a gas-phase catalytic synthesis reaction in the presence of a catalyst, wherein the catalyst includes the catalyst of the present invention.
[0014] Through the above technical scheme, the space-time yield of vinyl acetate products and the selectivity of vinyl acetate synthesis reaction can be effectively improved. DETAILED DESCRIPTION
[0015] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0016] In the present invention, the composition of each substance in the catalyst is calculated based on the input materials.
[0017] In the present invention, the Group IB metal in the catalyst mainly exists in the form of a single substance.
[0018] In the present invention, Pd mainly exists in the form of a single substance.
[0019] The present invention provides a catalyst for synthesizing vinyl acetate. The catalyst comprises a carrier and Pd, IB group metal and alkali metal acetate loaded on the carrier, wherein the ratio of the content of strong acid sites to the content of weak acid sites on the surface of the catalyst is 0.15-5, preferably 0.2-4.
[0020] In the present invention, there is no special requirement for the content of each substance, and the content commonly used in the art can be used in the present invention. The following is an exemplary description, but the scope of the present invention is not limited thereby.
[0021] According to one embodiment of the present invention, the content of Pd is 1 to 12 g / L, preferably 1 to 5 g / L, calculated as the element; for example, 1.1 g / L, 1.2 g / L, 1.3 g / L, 1.4 g / L, 1.5 g / L, 1.6 g / L, 1.7 g / L, 1.8 g / L, 1.9 g / L, 2.0 g / L, 2.1 g / L, 2.2 g / L, 2.3 g / L, 2.4 g / L, 2.5 g / L, 2.6 g / L, 2.7 g / L, 2.8 g / L, 2.9 g / L, 3 g / L, 3.1 g / L, 3.2 g / L, 3.3 g / L, 3.4 g / L, 3.5 g / L, 3.6 g / L, 3.7 g / L, 3.8 g / L, 3.9 g / L, 4.0 g / L, 4.1 g / L, 4.2 g / L, 4.3 g / L, 4.4 g / L, 4.5 g / L, 4.6 g / L, 4.7 g / L, 4.8 g / L, 4.9 g / L, and 5 g / L. This can improve the selectivity of the catalyst.
[0022] According to one embodiment of the present invention, the content of Group IB metal is 0.1-10 g / L, preferably 0.2-3 g / L, for example, 0.2 g / L, 0.3 g / L, 0.4 g / L, 0.5 g / L, 0.6 g / L, 0.7 g / L, 0.8 g / L, 0.9 g / L, 1 g / L, 1.1 g / L, 1.5 g / L, 1.6 g / L, 1.7 g / L, 1.8 g / L, 1.9 g / L, 2 g / L, 2.1 g / L, 2.5 g / L, 2.6 g / L, 2.7 g / L, 2.8 g / L, 2.9 g / L, 3 g / L, thereby improving the selectivity of the catalyst.
[0023] According to one embodiment of the present invention, the catalyst contains a phosphoric acid-containing substance, and the phosphoric acid-containing substance is preferably one or more of phosphoric acid and phosphorous acid, thereby improving the selectivity of the catalyst.
[0024] According to one embodiment of the present invention, preferably, the content of the phosphoric acid-containing substance is 5 to 500 mmol / L, preferably 10 to 300 mmol / L, thereby improving the selectivity of the catalyst.
[0025] According to one embodiment of the present invention, it is more preferred that the catalyst contains a phosphite additive, and the phosphite additive is selected from one or more of sodium phosphate and potassium phosphate, thereby improving the selectivity of the catalyst.
[0026] According to one embodiment of the present invention, preferably, the molar ratio of the phosphorus salt auxiliary agent to the phosphoric acid-containing substance is 0.005 to 0.5, preferably 0.01 to 0.1, thereby improving the selectivity of the catalyst.
[0027] According to one embodiment of the present invention, the content of alkali metal acetate is 10-100 g / L, preferably 20-50 g / L, for example 20 g / L, 30 g / L, 40 g / L, 40 g / L, thereby improving the selectivity of the catalyst.
[0028] In the present invention, all metals of Group IB can be used in the present invention, which is exemplified below, but the scope of the present invention is not limited thereby.
[0029] According to one embodiment of the present invention, for the present invention, the preferred Group IB metal is Au and / or Cu, preferably Au.
[0030] In the present invention, commonly used alkali metal elements can be used in the present invention. The following exemplary description is not intended to limit the scope of the present invention. According to one embodiment of the present invention, the alkali metal element is selected from one or more of Li, Na, K, Rb, Cs, and Fr, preferably one or more of Na and K; preferably, the alkali metal acetate is potassium acetate; thereby, the selectivity of the catalyst can be improved.
[0031] In the present invention, there is no special requirement for the carrier, and the carrier commonly used in the art can achieve the purpose of the present invention. The following exemplary description is not intended to limit the scope of the present invention. According to one embodiment of the present invention, the carrier is selected from one or more of silicon oxide and aluminum oxide. According to a preferred embodiment of the present invention, preferably, the carrier is selected from spherical silicon dioxide, preferably, the diameter of the spherical silicon dioxide is 2-8 mm, and the specific surface area is 150-200 m 2 / g, pore volume is 0.6-1cm 3 / g, the diameter of the spherical silica in the present invention is 5mm, and the specific surface area is 175m 2 / g, pore volume is 0.8cm 3 / g is used as an example to illustrate the advantages of the present invention, but the present invention is not limited to this.
[0032] The catalysts having the above-mentioned characteristics of the present invention can achieve the purpose of the present invention, and there is no special requirement for their preparation methods. According to the present invention, a preparation method of the catalyst for synthesizing vinyl acetate is provided, which comprises:
[0033] (a) immersing a catalyst support source in a solution containing a palladium source and a Group IB metal source, and drying to obtain a catalyst precursor I;
[0034] (b) mixing and contacting the catalyst precursor I with a solution of a basic compound, and drying to obtain a catalyst precursor II;
[0035] (c) reducing the metal ions of catalyst precursor II and drying to obtain catalyst precursor III;
[0036] (d) impregnating catalyst precursor III with alkali metal acetate and drying to obtain catalyst precursor IV;
[0037] (e) The catalyst precursor IV is immersed in an aqueous solution containing a phosphoric acid substance, and then dried to obtain a finished catalyst.
[0038] In the present invention, in step (e), the phosphoric acid-containing substance has a wide range of optional types, which are exemplified below, but are not limited to the scope of the present invention. According to one embodiment of the present invention, in step (e), the phosphoric acid-containing substance is a phosphorus oxyacid, preferably one or more of phosphoric acid and phosphorous acid. This can improve the selectivity of the catalyst.
[0039] According to a preferred embodiment of the present invention, preferably, step (e) is carried out in the presence of an auxiliary agent, preferably, the phosphate auxiliary agent is selected from one or more of sodium phosphate and potassium phosphate, and preferably the molar ratio of the phosphate auxiliary agent to the phosphoric acid-containing substance is 0.005 to 0.5, preferably 0.01 to 0.1; thereby, the selectivity of the catalyst can be improved.
[0040] In the present invention, in step (e), the concentration range of the solution of the phosphoric acid-containing substance is relatively wide, which is exemplified below, but is not limited to the scope of the present invention. According to one embodiment of the present invention, the content of the phosphoric acid-containing substance in the aqueous solution of the phosphoric acid-containing substance is 5 to 500 mmol / L, preferably 10 to 200 mmol / L, 10 mmol / L, 15 mmol / L, 100 mmol / L, 185 mmol / L, 200 mmol / L.
[0041] In the present invention, in step (e), the solid-liquid volume ratio can be selected in a wide range, which is exemplified below but is not limited to the scope of the present invention. The preferred solid-liquid volume ratio is 1:1-1:1.5. In the present invention, a solid-liquid volume ratio of 1.5 is used as an example to illustrate the advantages of the present invention.
[0042] In the present invention, in step (e), there is no special requirement for the immersion time, as long as sufficient immersion is achieved.
[0043] In the present invention, in step (e), there is no special requirement for the drying conditions, and common drying conditions can be applied to the present invention, which will not be described in detail herein. For example, the drying is generally carried out at 40-60° C., and there is no special requirement for the drying time.
[0044] According to one embodiment of the present invention, the conditions in step (a) include: a solid-liquid volume ratio of 1:1-1:1.2. In the present invention, a solid-liquid volume ratio of 1.2 is used as an example to illustrate the advantages of the present invention.
[0045] According to one embodiment of the present invention, the conditions in step (a) include: in the solution containing the Pd source and the Group IB metal source, the content of Pd, calculated as the element, is 1 to 12 g / L, preferably 2 to 3 g / L.
[0046] According to one embodiment of the present invention, the conditions in step (a) include: the content of Group IB metal is 0.1 to 10 g / L, preferably 0.4 to 0.8 g / L.
[0047] In the present invention, there is no special requirement for the carrier source, and any carrier source commonly used in the art can achieve the purpose of the present invention. The carrier source is selected from one or more of silicon dioxide and aluminum oxide; preferably, the carrier source is selected from spherical silicon dioxide, and preferably the diameter of the spherical silicon dioxide is 2-8 mm, and the specific surface area is 150-200 m 2 / g, pore volume is 0.6-1cm 3 / g.
[0048] In the present invention, the optional range of conditions in step (b) is relatively wide, and the conditions commonly used in the art can be used in the present invention. The following exemplary description does not limit the scope of the present invention. According to one embodiment of the present invention, the conditions in step (b) include: the concentration of the solution of the alkaline compound is 10-30% by weight.
[0049] According to one embodiment of the present invention, the conditions in step (b) include: the volume ratio of the solution of the basic compound to the carrier is 0.05 to 0.5, preferably 0.07 to 0.1.
[0050] In the present invention, the alkaline compound has a wide range of selectable types. According to a preferred embodiment of the present invention, in step (b), the alkaline compound includes but is not limited to one or more of sodium silicate and sodium hydroxide. According to the present invention, sodium silicate is preferred.
[0051] According to one embodiment of the present invention, the reducing agent used for reduction includes but is not limited to one or more of hydrazine hydrate and sodium citrate.
[0052] In the present invention, there are no special requirements for the conditions of reduction, optional water washing and drying. Commonly used reduction, water washing and drying conditions can be used in the present invention. According to a preferred embodiment of the present invention, the conditions in step (c) include: reduction time of 1-10 hours; water washing time of 1-20 hours; drying temperature of 60-100°C; drying time of 1-10 hours.
[0053] In the present invention, in step (d), the catalyst precursor III is impregnated with alkali metal acetate and dried to obtain the catalyst precursor IV; there is no special requirement for the impregnation conditions, and it can be carried out with reference to the prior art, for example, the solid-liquid volume ratio is 1:1 to 1.2; in the impregnation solution, the concentration of the alkali metal acetate is, for example, 5-50 g / L.
[0054] In the present invention, the purpose of drying is to remove liquid matter from the solid, and generally drying is performed so that the solid content is above 95 wt %.
[0055] In the present invention, the alkali metal acetate may be selected from a wide range of types, such as potassium acetate.
[0056] In the present invention, in steps (a) to (e), the process is allowed to stand as required in order to allow the solid and the liquid to fully contact each other.
[0057] In the present invention, step (a) can be optionally allowed to stand for 0.5-3 hours as required.
[0058] In the present invention, step (b) can be optionally allowed to stand for 12-24 hours as required.
[0059] In the present invention, step (c) can be optionally allowed to stand for 3-6 hours as required.
[0060] In the present invention, step (d) can be optionally allowed to stand for 3-6 hours as required.
[0061] In the present invention, step (e) can be optionally allowed to stand for 3-6 hours as required.
[0062] In the present invention, in steps (a) to (e), water washing is performed before drying as needed, and the purpose of water washing is to remove impurity ions such as chloride ions.
[0063] The present invention provides a method for synthesizing vinyl acetate. In the presence of a catalyst, raw gas for synthesizing vinyl acetate undergoes a gas phase catalytic synthesis reaction. The catalyst includes the catalyst of the present invention.
[0064] According to a preferred embodiment of the present invention, the raw gas for synthesizing vinyl acetate includes oxygen, ethylene, nitrogen and acetic acid; preferably, the raw gas composition in a molar ratio is oxygen:ethylene:nitrogen:acetic acid=1:(5-7):(4-8):(1-2).
[0065] According to a preferred embodiment of the present invention, the conditions for the gas phase catalytic synthesis reaction include: the reaction pressure is 0.5 to 0.9 MPa.
[0066] According to a preferred embodiment of the present invention, the conditions for the gas phase catalytic synthesis reaction include: a reaction temperature of 130-200°C, for example, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C.
[0067] According to a preferred embodiment of the present invention, the conditions for the gas phase catalytic synthesis reaction include: the raw gas volume space velocity is 1600 to 3000 hr -1 .
[0068] In the present invention, unless otherwise specified, the operation is carried out at room temperature.
[0069] In the present invention, unless otherwise specified, the solvent of the solution is water.
[0070] In the present invention, the catalyst surface acid site testing method is:
[0071] The acid sites on the catalyst surface can be detected by NH3-TPD. The desorption temperature of NH3-TPD represents the strength of the acid sites. Desorption at low temperature represents weak acid sites, and desorption at high temperature represents strong acid sites. The peak area can represent the amount of acid sites. The strong / weak acid site content ratio is calculated based on the area ratio of the high-temperature desorption peak (strong acid site) >400℃ and the low-temperature desorption peak (weak acid site) <400℃.
[0072] The test conditions of NH3-TPD: the sample was first purged with helium at 50°C for 30 minutes (space velocity of 300 ml / min), then switched to NH3 to purge the sample for 2 hours (space velocity of 300 ml / min), and then the temperature was increased gradually (heating rate of 5°C / min), and the temperature investigation range was selected from 100-750°C.
[0073] The calculation method of catalyst space time yield (STY) and selectivity (SEL) is:
[0074] Assume: A is the amount of ethylene reacted in one day (kmol / d), B is the amount of oxygen reacted in one day, and X is the amount of ethylene consumed by the main reaction in one day.
[0075] X = (3A - B) / 2.5.
[0076] STY = 86X / catalyst amount (m 3 )×1000.
[0077] SEL=X / A×100%.
[0078] Example 1
[0079] 1. Catalyst preparation
[0080] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 2.75 g / L, and the content of gold was 0.625 g / L, and dried at 60° C. for 8 h to obtain a catalyst precursor I;
[0081] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0082] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0083] (d) impregnating the catalyst precursor III with a potassium acetate aqueous solution (potassium acetate content of 30 g / L) at a solid-liquid volume ratio of 1 for 6 hours, and drying at 80° C. for 2 hours to obtain a catalyst precursor IV;
[0084] (e) The catalyst precursor IV was immersed in a phosphoric acid aqueous solution (phosphoric acid concentration was 10 mmol / L) at a solid-liquid volume ratio of 1:1.5 for 24 hours, and then dried at 50° C. to obtain a finished catalyst.
[0085] 2. Catalyst evaluation
[0086] The fixed bed reactor was used for evaluation, and the specific conditions were:
[0087] Catalyst filling volume: 40ml;
[0088] The composition of the reaction raw materials (by molar ratio): oxygen: ethylene: nitrogen: acetic acid = 1: 6.5: 7.4: 1.6;
[0089] Reaction raw material feed volume space velocity: 1950hr -1 ;
[0090] Reaction pressure: 0.7MPa;
[0091] Reaction temperature: 138°C;
[0092] Reaction time: 100hr;
[0093] The content of each component in the reaction product was analyzed by gas chromatography, and then the space-time yield and ethylene selectivity of the catalyst were calculated.
[0094] For the convenience of comparison, the experimental results are listed in Table 1.
[0095] Example 2
[0096] 1. Catalyst preparation
[0097] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 2.75 g / L, and the content of gold was 0.625 g / L, and dried at 60° C. for 8 h to obtain a catalyst precursor I;
[0098] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0099] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0100] (d) impregnating the catalyst precursor III with a potassium acetate aqueous solution (potassium acetate content of 30 g / L) for 6 hours at a solid-liquid volume ratio of 1, and drying at 80° C. for 2 hours to obtain a catalyst precursor IV;
[0101] (e) The catalyst precursor IV was immersed in a phosphoric acid aqueous solution (phosphoric acid concentration was 100 mmol / L) at a solid-liquid volume ratio of 1:1.5 for 24 hours, and then dried at 50° C. to prepare a finished catalyst.
[0102] 2. Catalyst evaluation
[0103] The catalyst evaluation method was the same as in Example 1.
[0104] For the convenience of comparison, the experimental results are listed in Table 1.
[0105] Example 3
[0106] 1. Catalyst preparation
[0107] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 2.75 g / L, and the content of gold was 0.625 g / L, and dried at 60° C. for 8 h to obtain a catalyst precursor I;
[0108] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0109] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0110] (d) impregnating the catalyst precursor III with a potassium acetate aqueous solution (potassium acetate content of 30 g / L) at a solid-liquid volume ratio of 1 for 6 hours, and drying at 80° C. for 2 hours to obtain a catalyst precursor IV;
[0111] (e) The catalyst precursor IV was immersed in a phosphoric acid aqueous solution (phosphoric acid concentration was 200 mmol / L) at a solid-liquid volume ratio of 1:1.5 for 24 hours, and then dried at 50° C. to prepare a finished catalyst.
[0112] 2. Catalyst evaluation
[0113] The catalyst evaluation method was the same as in Example 1.
[0114] For the convenience of comparison, the experimental results are listed in Table 1.
[0115] Example 4
[0116] 1. Catalyst preparation
[0117] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 2.75 g / L, and the content of gold was 0.625 g / L, and dried at 60° C. for 8 h to obtain a catalyst precursor I;
[0118] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0119] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0120] (d) impregnating the catalyst precursor III with a potassium acetate aqueous solution (potassium acetate content of 30 g / L) at a solid-liquid volume ratio of 1 for 6 hours, and drying at 80° C. for 2 hours to obtain a catalyst precursor IV;
[0121] (e) The catalyst precursor IV was immersed in a phosphorous acid aqueous solution (phosphoric acid concentration was 100 mmol / L) at a solid-liquid volume ratio of 1:1.5 for 24 hours, and then dried at 50° C. to prepare a finished catalyst.
[0122] 2. Catalyst evaluation
[0123] The catalyst evaluation method was the same as in Example 1.
[0124] For the convenience of comparison, the experimental results are listed in Table 1.
[0125] Example 5
[0126] 1. Catalyst preparation
[0127] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 2.75 g / L, and the content of gold was 0.625 g / L, and dried at 60° C. for 8 h to obtain a catalyst precursor I;
[0128] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0129] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0130] (d) impregnating the catalyst precursor III with a potassium acetate aqueous solution (potassium acetate content of 30 g / L) at a solid-liquid volume ratio of 1 for 6 hours, and drying at 80° C. for 2 hours to obtain a catalyst precursor IV;
[0131] (e) The catalyst precursor IV was immersed in a phosphorous acid aqueous solution (phosphoric acid concentration was 185 mmol / L) at a solid-liquid volume ratio of 1:1.5 for 24 hours, and then dried at 50° C. to obtain a finished catalyst.
[0132] 2. Catalyst evaluation
[0133] The catalyst evaluation method was the same as in Example 1.
[0134] For the convenience of comparison, the experimental results are listed in Table 1.
[0135] Example 6
[0136] 1. Catalyst preparation
[0137] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 2.75 g / L, and the content of gold was 0.625 g / L, and dried at 60° C. for 8 h to obtain a catalyst precursor I;
[0138] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0139] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0140] (d) impregnating the catalyst precursor III with a potassium acetate aqueous solution (potassium acetate content of 30 g / L) at a solid-liquid volume ratio of 1 for 6 hours, and drying at 80° C. for 2 hours to obtain a catalyst precursor IV;
[0141] (e) The catalyst precursor IV was immersed in a phosphorous acid aqueous solution (phosphoric acid concentration was 15 mmol / L) at a solid-liquid volume ratio of 1:1.5 for 24 hours, and then dried at 50° C. to obtain a finished catalyst.
[0142] 2. Catalyst evaluation
[0143] The catalyst evaluation method was the same as in Example 1.
[0144] For the convenience of comparison, the experimental results are listed in Table 1.
[0145] Example 7
[0146] 1. Catalyst preparation
[0147] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 2.75 g / L, and the content of gold was 0.625 g / L, and dried at 60° C. for 8 h to obtain a catalyst precursor I;
[0148] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0149] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0150] (d) impregnating the catalyst precursor III with a potassium acetate aqueous solution (potassium acetate content of 30 g / L) at a solid-liquid volume ratio of 1 for 6 hours, and drying at 80° C. for 2 hours to obtain a catalyst precursor IV;
[0151] (e) The catalyst precursor IV was immersed in a mixed aqueous solution of phosphoric acid and sodium phosphate (the phosphoric acid concentration was 100 mmol / L, the sodium phosphate concentration was 10 mmol / L) at a solid-liquid volume ratio of 1:1.5 for 24 hours, and then dried at 50° C. to prepare a finished catalyst.
[0152] 2. Catalyst evaluation
[0153] The catalyst evaluation method was the same as in Example 1.
[0154] For the convenience of comparison, the experimental results are listed in Table 1.
[0155] Example 8
[0156] 1. Catalyst preparation
[0157] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 2.75 g / L, and the content of gold was 0.625 g / L, and dried at 60° C. for 8 h to obtain a catalyst precursor I;
[0158] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0159] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0160] (d) impregnating the catalyst precursor III with a potassium acetate aqueous solution (potassium acetate content of 30 g / L) for 6 hours at a solid-liquid volume ratio of 1, and drying at 80° C. for 2 hours to obtain a catalyst precursor IV;
[0161] (e) The catalyst precursor IV was immersed in a mixed aqueous solution of phosphoric acid and potassium phosphate (the phosphoric acid concentration was 100 mmol / L and the sodium phosphate concentration was 1 mmol / L) at a solid-liquid volume ratio of 1:1.5 for 24 hours, and then dried at 50° C. to prepare a finished catalyst.
[0162] 2. Catalyst evaluation
[0163] The catalyst evaluation method was the same as in Example 1.
[0164] For the convenience of comparison, the experimental results are listed in Table 1.
[0165] Comparative Example 1
[0166] 1. Catalyst preparation
[0167] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 2.75 g / L, and the content of gold was 0.625 g / L, and dried at 60° C. for 8 h to obtain a catalyst precursor I;
[0168] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0169] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0170] (d) Catalyst precursor III was impregnated with potassium acetate aqueous solution (potassium acetate content was 30 g / L) at a solid-liquid volume ratio of 1 for 6 hours and dried at 80°C for 2 hours to obtain a finished catalyst, so that the potassium acetate content in the catalyst was 30 g / L.
[0171] 2. Catalyst evaluation
[0172] The catalyst evaluation method was the same as in Example 1.
[0173] For the convenience of comparison, the experimental results are listed in Table 1.
[0174] Table 1
[0175]
[0176] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalyst for synthesizing vinyl acetate, characterized in that: The catalyst comprises a carrier and Pd, IB group metal and alkali metal acetate loaded on the carrier, wherein the ratio of the content of strong acid sites to the content of weak acid sites on the surface of the catalyst is 0.15-5, preferably 0.2-4.
2. The catalyst according to claim 1, wherein The content of Pd is 1 to 12 g / L, preferably 1 to 5 g / L, calculated as the element.
3. The catalyst according to claim 1 or 2, wherein Calculated as an element, the content of Group IB metal is 0.1 to 10 g / L, preferably 0.2 to 3 g / L; and / or The Group IB metal is Au and / or Cu, preferably Au; and / or The catalyst contains a phosphoric acid-containing substance, and the phosphoric acid-containing substance is preferably one or more of phosphoric acid and phosphorous acid; Preferably, the content of the phosphoric acid-containing substance is 5 to 500 mmol / L, preferably 10 to 300 mmol / L; More preferably, the catalyst contains a phosphonium salt additive, wherein the phosphonium salt additive is selected from one or more of sodium phosphate and potassium phosphate; Preferably, the molar ratio of the phosphate auxiliary agent to the phosphoric acid-containing substance is 0.005 to 0.5, preferably 0.01 to 0.
1.
4. The catalyst according to any one of claims 1 to 3, wherein The content of the alkali metal acetate is 10 to 100 g / L, preferably 20 to 50 g / L.
5. The catalyst according to any one of claims 1 to 4, wherein The alkali metal element is selected from one or more of Li, Na, K, Rb, Cs and Fr, preferably one or more of Na and K; preferably, the alkali metal acetate is potassium acetate; and / or The carrier is selected from one or more of silicon oxide and aluminum oxide; Preferably, the carrier is selected from spherical silica, preferably the diameter of the spherical silica is 2-8 mm and the specific surface area is 150-200 m 2 / g, pore volume is 0.6-1cm 3 / g.
6. A method for preparing a catalyst for synthesizing vinyl acetate according to any one of claims 1 to 5, characterized in that: The method includes: (a) immersing a catalyst support source in a solution containing a palladium source and a Group IB metal source, and drying to obtain a catalyst precursor I; (b) mixing and contacting the catalyst precursor I with a solution of a basic compound, and drying to obtain a catalyst precursor II; (c) reducing the metal ions of catalyst precursor II and drying to obtain catalyst precursor III; (d) impregnating catalyst precursor III with alkali metal acetate and drying to obtain catalyst precursor IV; (e) The catalyst precursor IV is immersed in an aqueous solution containing a phosphoric acid substance, and then dried to obtain a finished catalyst.
7. The method according to claim 6, wherein: In step (e), The phosphorus acid-containing substance is a phosphorus oxyacid, preferably one or more of phosphoric acid and phosphorous acid; Preferably, step (e) is carried out in the presence of a phosphate auxiliary agent, preferably, the phosphate auxiliary agent is selected from one or more of sodium phosphate and potassium phosphate; Preferably, the molar ratio of the amount of the phosphate additive to the amount of the phosphoric acid-containing substance is 0.005 to 0.5, preferably 0.01 to 0.1; and / or The phosphoric acid-containing substance aqueous solution has a phosphoric acid-containing substance content of 5 to 500 mmol / L, preferably 10 to 200 mmol / L; and / or The solid-liquid volume ratio is 1:1-1.
5.
8. The preparation method according to claim 6 or 7, wherein: The conditions in step (a) include: a solid-liquid volume ratio of 1:1-1.2, a Pd content of 1-12 g / L, preferably 2-3 g / L, in the solution containing a Pd source and a Group IB metal source, calculated as an element; and a Group IB metal content of 0.1-10 g / L, preferably 0.4-0.8 g / L; In step (a), the carrier source is selected from one or more of silicon dioxide and aluminum oxide; Preferably, the carrier source is selected from spherical silica, preferably the diameter of the spherical silica is 2-8 mm and the specific surface area is 150-200 m 2 / g, pore volume is 0.6-1cm 3 / g; and / or The conditions in step (b) include: the concentration of the alkaline compound solution is 10-30% by weight, and the volume ratio of the alkaline compound solution to the carrier is 0.05-0.5, preferably 0.07-0.1; and / or In step (b), the alkaline compound is selected from one or more of sodium silicate and sodium hydroxide.
9. A method for synthesizing vinyl acetate, wherein a raw material gas for synthesizing vinyl acetate is subjected to a gas phase catalytic synthesis reaction in the presence of a catalyst, characterized in that: The catalyst comprises the catalyst according to any one of claims 1 to 5.
10. The synthesis method according to claim 9, wherein The raw gas for synthesizing vinyl acetate includes oxygen, ethylene, nitrogen and acetic acid; preferably, In terms of molar ratio, the molar ratio of oxygen, ethylene, nitrogen and acetic acid is 1:(5-7):(4-8):(1-2); and / or The conditions for the gas phase catalytic synthesis reaction include: The reaction pressure is 0.5-0.9 MPa, and / or The reaction temperature is 130-200°C, and / or The raw gas volume space velocity is 1600~3000hr -1 .
Citation Information
Patent Citations
Highly selective shell impregnated catalyst of improved space time yield for production of vinyl acetate
CN101391215A
Carrier catalyst, process for preparation and use
CN1068051A
Preparation method of catalyst used for vinyl acetate production
CN112517063A
Preparation of vinyl acetate
CN1239942A
Production of Vinyl Acetate.
GB1176743A